ANALISIS KEMAMPUAN NUMERASI SISWA SMA DITINJAU DARI TIPE KEPRIBADIAN EXTROVERT DAN INTROVERT - Sari, Fanny Fradhinka; Wahidin, Wahidin (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2022)
The purpose of this study is to analyze the numeracy skills of high school students in solving AKM questions in terms of the extrovert-introvert personality type. The method in this study is a descriptive method with a qualitative approach. The subjects of this study were 6 students from class X IPA in one of the public high schools in North Jakarta who were taken using a purposive random sampling technique with three students each from the extroverted personality type and three other students from the introverted personality type, which was measured using the theory of Eysenck's personality is the Eysenck Personality Inventory (EPI). There are 3 indicators that meet numeracy abilities. The results of this study indicate that Extrovert students have lower numeracy skills than Introvert students. Extrovert students can meet 2 ability indicators while Introvert students can meet 3 ability indicators.